A handy reversible bonding technology and its application on fabrication of an on-chip liquid metal micro-thermocouple. Issue 23 (22nd October 2021) - Hong, Jie; Gong, Jiahao; Li, Qian; Deng, Zhongshan; Gui, Lin
Abstract : An on-chip liquid metal based micro-thermocouple based on a reversible bonding technology. Abstract : We report a novel reversible bonding technique for liquid metal (LM) microelectrode fabrication in this study. This technique greatly simplifies the process of LM micro-electrode fabrication and can be used to achieve the rapid fabrication of LM blind-end electrodes. Three kinds of treatments, including heat treatment, plasma treatment and heat/plasma treatment, were tested for bonding strength. The experimental results showed that the heat/plasma treatment has the strongest bonding strength. All the three treatments can be completely released by simple water treatment. This handy fabrication method can help to integrate micro-liquid metal electrodes vertically in a microchannel. At the end of this work, this fabrication method was used to integrate liquid metal thermocouples in a microchannel, which greatly shortened the fabrication time and lowered the cost compared with traditional deposition or sputtering methods.